IS There an Impact of PAI-1 on the Thrombotic Episode in Iraqi Obese Patients with Corona Virus -19 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: firstly To assess the incidence of Corona Virus -19 covid-19 as risk factors in obese individualsleading to thrombotic episode, and secondly to compare the effects Plasminogen activator inhibitor-1 (PAI-1)on the occurrence of this thrombotic status in obese and normal body weight individuals. The pathogenesisof Coronavirus disease 2019 (COVID-19) is gradually demonstrated and explained around the world A highand a great number of thrombotic episodes are reported, in present study can be consider the COVID-19 asa prothrombotic disease.Design and Methods: The experiments comparing the PAI-1 in 90 obese and 30 normal body weightparticipants aged 32-62 years. The obese patients subdivided to three groups: first group consisted from 30over weight individuals and the second group comprised from 30 obese patients, while third group consistedfrom 30 morbid obesity patients. All participants underwent to the medical examinations to make sure theywere infected with covid-19. The activity of PAI-1and tissue plasminogen activator (t-PA) was determinedby applied ELISA method by certain kit in all study groups individuals.Results: Three study groups (overweight, obese, and morbid obesity) elicited significant (p< 0.05) elevationin metabolic characteristics such as fasting blood glucose (FBG), fasting insulin and lipids variables, as wellas increasing in insulin resistance (HOMA-IR) and D-dimer fractions, in addition to there were significantaugmentation in PAI-1 and t-PA in three study groups when comparing with those of normal or healthy bodyweightThe present results show a positive relationship between PAI-1 and body mass index, t-PA, D-dimer andmetabolic characteristics which include fasting blood glucose, fasting insulin and lipids fractions, alsoHOMA-IR.
Keywords: Covid-19, Obesity, PAI-1 , t-PA, thrombosis